The Legal Regulation of the Carrier in Autonomous Vehicles - Abbas Razzooqee Al-Ibraheemi, Assist. Lect. Dhulfiqar (Basra studies journal, 2025)
This study explores an issue that has become central to contemporary legal discourse: the responsibility and obligations of the carrier in autonomous vehicles. It seeks to identify an appropriate legal framework to regulate this relationship and examines mechanisms for protecting both the carrier and the passenger, particularly given the absence of any specific regulation in Iraqi legislation. The study further aims to develop a legal structure suitable for the Iraqi context by clarifying the carrier’s responsibilities and obligations in self-driving transport systems, as well as proposing mechanisms that may exempt the carrier from liability under certain circumstances. The findings emphasize the necessity of enacting legal provisions that clearly define autonomous vehicles and delineate the respective duties and obligations of both the carrier and the passenger.